QUALITY AND ACCEPTANCE OF SOFT CHEESE MADE OF FRIES HOLLAND MILK WITH ADDED STRAWBERRY (Fragaria virginiana) PASTA DURING 2 WEEKS OF STORAGE - Rielni Love Rati; Endang Sulistyowati; Edi Soetrisno (Jurnal Agroindustri, 2017)
This research aimed to evaluate the effect of added strawberry (Fragaria virginiana) in soft cheese on quality of dry matter), Total Plate Count (TPC) and acceptance of consumer during storage of 2 weeks. This research was conducted in Merch- April 2017 in Animal Science Laboratory and Ilmu Hama dan Penyakit Tanaman (IHPT) Laboratory, Faculty of Agriculture, University of Bengkulu. There were 4 treatments and 4 replication,  P0: cheese with 0% strawberry pasta, P1: cheese with 1% strawberry pasta, P2: cheese with 3% strawberry pasta, P3: cheese with 5% strawberry pasta. Variables evaluated were quality and acceptance.  Results showed that added strawberry (Fragaria virginiana) pasta showed no significant (P>0.05) effects during storage of 2- 4 weeks on dry matter, the highest TPC was found in cheese with 0% strawberry pasta; while, organoleptic test showed very significant effects (P<0.001) on color, aroma and taste of the cheese, however, it was no significant effects (P>0.05) on texture and acceptance.Keywords :